2003
DOI: 10.1021/ci034110b
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic QSAR Methods and Self-Organizing Molecular Field Analysis for Relating Molecular Structure and Estrogenic Activity

Abstract: The performance of three "spectroscopic" quantitative structure-activity relationship (QSAR) methods (eigenvalue (EVA), electronic eigenvalue (EEVA), and comparative spectra analysis (CoSA)) for relating molecular structure and estrogenic activity are critically evaluated. The methods were tested with respect to the relative binding affinities (RBA) of a diverse set of 36 estrogens previously examined in detail by the comparative molecular field analysis method. The CoSA method with (13)C chemical shifts appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A comparative QSAR study was also performed by Asikainen et al with respect to the RBA for a diverse set of 36 estrogens to ER using three “spectroscopic” QSAR methods: eigenvalue (EVA), electronic eigenvalue (EEVA), and comparative spectra analysis (CoSA). The statistical parameters of different QSDAR models and the number of principal components (PCs) used in their development are shown in Table .…”
Section: Qsar Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative QSAR study was also performed by Asikainen et al with respect to the RBA for a diverse set of 36 estrogens to ER using three “spectroscopic” QSAR methods: eigenvalue (EVA), electronic eigenvalue (EEVA), and comparative spectra analysis (CoSA). The statistical parameters of different QSDAR models and the number of principal components (PCs) used in their development are shown in Table .…”
Section: Qsar Results and Discussionmentioning
confidence: 99%
“…The EEVA model is in the borderline, whereas the performances of the EVA and CoSA models with 1 H NMR chemical shifts are substandard. On the basis of this comparative QSAR study, the authors suggested that the CoSA method with 13 C NMR chemical shifts is an alternative to the conventional 3D-QSAR methods for rationalizing and predicting the estrogenic activities of molecules …”
Section: Qsar Results and Discussionmentioning
confidence: 99%
“…Identification of individual signals in NMR spectra of complex mixtures can be assisted by structure-based predictions. Accurate predictions of NMR spectra enable the calibration of spectra-property relationships and chemometric models, exclusively on the basis of simulated data, which can then be applied to experimental data. , …”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR and 13 C NMR spectra have been used in several QSAR and QSPR studies. Three different methods have been used in those studies to include NMR descriptors, although other approaches can be considered too. Most used is the whole spectrum approach. , As explained in the previous paragraph, shift areas will then correlate with the modeled activity. Optionally, specific features of the spectrum can be selected, for example, a few areas where relevant information is found.…”
Section: Introductionmentioning
confidence: 99%